Factors affecting perioperative mortality in tetralogy of Fallot. Issue 5 (29th May 2015) - Saygi, Murat; Ergul, Yakup; Tola, Hasan Tahsin; Ozyilmaz, Isa; Ozturk, Erkut; Onan, Ismihan Selen; Haydin, Sertac; Erek, Ersin; Yeniterzi, Mehmet; Guzeltas, Alper; Odemis, Ender; Bakir, Ihsan
Abstract: Background: We evaluated the preoperative, operative and postoperative risk factors affecting early mortality in patients who underwent total correction of tetralogy of Fallot (TOF). Methods: One hundred and twenty‐two TOF patients who underwent reparative surgery between January 2010 and November 2013 were enrolled in the study. Results: Mean patient age and weight was 2.3 ± 2.5 years and 11.3 ± 6.4 kg, respectively. Cardiac catheterization was performed in 101 patients (83%), and coronary anomalies were found in 11 patients. Mean McGoon index, pulmonary annulus z‐score, main pulmonary artery z‐score, left pulmonary artery z‐score and right pulmonary artery z‐score were 2.0 ± 0.4, –1.85 ± 1.54, –2.84 ± 2.06, 1.17 ± 1.73, and 0.74 ± 1.57, respectively. Total reparative surgery with a transannular patch was performed in 97 patients (79.6%); the rest underwent valve‐sparing surgery. Median duration of postoperative mechanical ventilation, intensive care and hospital stay were 19 h, 3 days and 9 days, respectively. Extracorporeal membrane oxygenation (ECMO) was required in 10 patients in the postoperative early period. Arrhythmias occurring in the early postoperative period were junctional ectopic tachycardia (n = 13), complete atrioventricular block(n = 10; permanent epicardial pacemaker implanted in four) and ventricular tachycardia (n = 4). Nine patients died in the early postoperative period (7.3%). Parameters found to be associated with increased mortality were low preoperative oxygen saturation; high right ventricular/aortic pressure ratio immediately after surgery; presence of coronary anomaly; requirement of postoperative ECMO; and pacemaker ( P = 0.02, P = 0.04, P = 0.01, P = 0.0001, P = 0.03, respectively). Conclusions: Poor preoperative oxygenation, presence of coronary anomaly, complete AV block in the early postoperative period, high RV pressure and requirement of ECMO appear to be the most significant factors that affect early mortality in the surgical treatment of TOF. Appropriate preoperative assessment, correct surgical strategies and attentive intensive care monitoring are required in order to reduce mortality.